Project Performance Through an Occupational and Health Safety Management System at an Office Building Project in Lampung Indonesia - Purwanto, Agustinus Hariadi Djoko; Hartono, Sri (Jurnal Manajemen Teknologi, 2022)
Abstract. A project contractor may fail to deliver on time, quality, and budget expectations due to incidents resulting in injuries and fatalities, as well as asset damage, elevated costs, and delays. This research aims to gauge a business improvement model on OHS (occupational and health safety) performance developed from operation standardization, communication, competency, hazard identification, and management commitment. Commitment initiates risk analysis for developing standardization, communication, and competency to achieve OHS performance. The present case study concerns a contractor establishing a local government office building in Lampung. It takes 100 respondents as a sample out of the 124 personnel in this construction project, relying on a quantitative method which processes data via PLS software to obtain the direction and magnitude of variable influences. OHS policy exhibits influence at 0.587 on HIRADC (Hazard Identification Risk Analysis and Determining Control); it affects standardization, competency, and communication at the values of 0.704, 0.450, and 0.300. The three variables then simultaneously affect OHS performance at the values of 0.540, 0.065, and 0.116. OHS performance affects business performance at a value of 0.384.Keywords: Hazard identification; ohs performance; business performance; competency; communication; management commitmentAbstrak. Sebuah kontraktor proyek mengalami kegagalan pada sasaran tepat waktu, kualitas dan biaya terendah menyebabkan insiden yang mengakibatkan luka dan kematian termasuk kerusakan aset, biaya bertambah, dan keterlambatan. Penelitian ini bertujuan untuk mengamati model peningkatan bisnis melalui kinerja K3 yang dikembangkan dari standar operasi, komunikasi, kompetensi, identifikasi bahaya dan komitment manajemen. Komitmen menginisiasi analisa risiko untuk sumber pengembangan standarisasi, komunikasi dan kompetensi dalam mencapai kinerja K3. Kontraktor menjalankan proyek pembangunan kantor pemerintah daerah di Lampung. Studi ini memperoleh sampel 100 responden dari populasi 124 personil. Aplikasi PLS dipakai untuk memproses data dalam mendapatkan arah dan besaran pengaruh variabel. Komitmen K3 memberikan pengaruh 0.587pada HIRADC darinya mempengaruhi Standarisasi, Kompetensi dan Komunikasi pada nilai 0.704, 0.450 dan 0.300. Ketiga variabel secara simultan mempengaruhi Kinerja K3 masing-masing pada nilai 0.540, 0.065 dan 0.116. Kinerja K3 mempengaruhi Kinerja bisnis pada besaran 0.384.Kata kunci: Hazard identification; ohs performance; business performance; competency; communication; management commitment